PEMAHAMAN KONSEPTUAL DAN IMPLIKASI RIBA DARI PERSPEKTIF EKONOMI SYARIAH - Syaila Salsabila; Cyntya Dwi Permata; Muhammad Farhan Mochtar; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Conceptual understanding of riba and its influence in Islamic economics is an important subject in the context of Islamic finance. This research highlights the conceptual understanding of riba and its implications from the perspective of Islamic economics. Through a literature review approach, this article explores various views and arguments related to riba in Islam and Islamic economics. The analysis in this article underscores the need for a deep understanding of riba in the context of Islamic economics. Through this approach, policies can be formulated to promote principles of justice, equality, and sustainability in the Islamic financial system. Practical implications include profit-sharing systems such as mudharabah and musyarakah being used to replace riba practices, ensuring fairness and equality among parties involved in transactions. Additionally, a deeper understanding of Sharia economics and strict supervision of riba practices in the financial sector are crucial to assist individuals and institutions in managing finances in accordance with Islamic law. In conclusion, the conceptual understanding of riba and its influence from the perspective of Islamic economics is an important aspect in building a financial system that aligns with Islamic principles. By understanding the implications of riba, society can take more sustainable and equitable steps in developing Sharia-based economies.